Tinjauan Hukum Terhadap Industri Rumah Tangga di Sentra Kripik Tempe Sanan - risya nabila (Journal of Islamic Business Law, 2018)
This study aims to determine Application of Home Industry Food Safety at Sanan Tempe Chip center, Malang City in prespective of act number 18 years 2012 and Islamic Law. This type of research is empirical law research using sociological juridical approach method dan statute approach. Method of collecting primary data through direct interview. In this research are summarized as follows: 1) Home Industry Food Safety at Sanan Tempe Chips Center have not been completely fulfilled the rules in the act number 18 years 2012 about food, especially in terms of food sanitation and food guarantee and food quality. Because in the act number 18 years 2012 in food safety section there are 7 food safety standart variable must be fulfill by enterpreneur in food sector; 2) in the view of Islamic law, particularly according Maqashid Sharia of food safety needs to be improved oversight so that the two sides in terms of food product safety no one is harmed.